2016
DOI: 10.1016/j.anireprosci.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma proteins interacting with sperm surface revert capacitation indicators in frozen-thawed ram sperm

Abstract: This study was conducted to evaluate the effects of interacting seminal plasma proteins (iSPP) obtained by AV or EE on frozen-thawed ram sperm in order to test the hypothesis whether this fraction could be sufficient to emulate the effect of complete seminal plasma (SP). Additionally, we evaluated whether these proteins have a differential effect between spermatozoa from high and low fertility rams and between breeding and non-breeding seasons. We assessed sperm motility, quality parameters (intracellular reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…Even though post-thaw sperm motility is a good indicator of viability, it is not always an accurate fertility predictor of an AI-semen dose [9]. Evaluations of sperm motility characteristics have been improved by the incorporation of the computer-assisted semen analysis (CASA) system, which measures several motility and motion parameters of spermatozoa that are closely related to fertility compared with subjective motility measurements [21][22][23][24]. Besides motility analysis, studies have conirmed that the velocity parameters, such as velocity straight line (VSL), velocity curvilinear (VCL), and velocity average path (VAP), are associated with the fertilizing capacity of frozen-thawed spermatozoa [21,24].…”
Section: Motility and Motion Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Even though post-thaw sperm motility is a good indicator of viability, it is not always an accurate fertility predictor of an AI-semen dose [9]. Evaluations of sperm motility characteristics have been improved by the incorporation of the computer-assisted semen analysis (CASA) system, which measures several motility and motion parameters of spermatozoa that are closely related to fertility compared with subjective motility measurements [21][22][23][24]. Besides motility analysis, studies have conirmed that the velocity parameters, such as velocity straight line (VSL), velocity curvilinear (VCL), and velocity average path (VAP), are associated with the fertilizing capacity of frozen-thawed spermatozoa [21,24].…”
Section: Motility and Motion Characteristicsmentioning
confidence: 99%
“…In recent years, several luorescent probes have shown that the cryopreservation process compromises the sperm plasma membrane integrity (PMI), resulting in reduced fertilizing capacity of postthaw semen [3][4][5][23][24][25][26][27][28][29]. Post-thaw sperm PMI has been assessed with diferent luorescent membrane probes, such as the dual SYBR-14 and propidium iodide (PI) assay [25,28] or membrane-permeable substrate carboxyluorescein diacetate (CFDA), a nonspeciic esterase substrate [24].…”
Section: Membrane Integritymentioning
confidence: 99%
See 3 more Smart Citations